Body composition differences in elite waterpolo players - Ozkol, Z.; Turunc, S.; Dopsaj, M. (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
INTRODUCTION: The aim of the present study was to investigate body composition differences in three different group elite water polo players. METHODS: All players representative of Turkiye National Waterpolo Team, totaly 163 waterpolo player investigated. First group consists of 18 senior water polo player age of 24.3±4.9 (SGRP), second group consists of 73 junior water polo player age group of 15-16 (JGRP) and the third group consists of 62 youth waterpolo player age group of 13-14 (YGRP). Body composition analysis made with Tanita BC- 418 Segmental Body Composition Analyzer (Tanita Corp., Tokyo, Japan) by BIA. All players analyzed at the begining of the national teams preparation period at 2009-2010. Data analyzed with PC using statistic software program SPSS for Win, 11.0.0 - SPSS Inc., 1989-2001) and the p value set at 0.05 significant level. RESULTS: At the results, differences were found between these three waterpolo player group at the following body composition parameters (p<0.05); height, body mass, basal metabolic rate, fat mass, fat free mass, total body water, right leg fat free mass, right leg predicted muscle mass, left leg fat free mass, left leg predicted muscle mass, right arm fat ratio, right arm fat free mass, right arm predicted muscle mass, left arm fat ratio, left arm fat free mass, left arm predicted muscle mass, truncal fat mass, truncal fat free mass and truncal predicted muscle mass. DISCUSSION: The present study provides baseline physiological data that have been used in the prescription of individual training programs (weight loss programs or strenght training) for these waterpolo players and this information is also available to the coaches.